The integer cohomology of toric Weyl arrangements - Simona Settepanella (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
A toric arrangement is a finite set of hypersurfaces in a complex torus, every hypersurface being the kernel of a character. In the present paper we prove that if TW is the toric arrangement defined by the cocharacters lattice of a Weyl group W, then the integer cohomology of its complement is torsion free.
Keywords: 330; arrangement of hyperplanes; toric arrangements; CW complexes; Salvetti complex; Weyl groups; integer cohomology; Mathematische Optimierung; Flugzeug; Luftfahrttechnik